Mechanics of hydraulic fracturing - Yew, Ching H. (Elsevier, 2015)
Revised to include current components considered for today's unconventional and multi-fracture grids, this edition explains one of the most important features for fracture design - the ability to predict the geometry and characteristics of the hydraulically induced fracture. This book will help you: understand complex fracture networks to maximize completion strategies; recognize and compute stress shadow, which can drastically affect fracture network patterns; optimize completions by properly modeling and more accurately predicting for today's hydraulic fracturing completions. The book discusses the underlying mechanics of creating a fracture from the wellbore and is enhanced to include newer modeling components such as stress shadow and interaction of hydraulic fracture with a natural fracture, which aids in more complex fracture networks. Updated experimental studies that apply to today's unconventional fracturing cases are supplied. --